2013
DOI: 10.1149/2.008308jes
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Electrodes with Low Platinum Loading for High Power Hydrogen/Air PEM Fuel Cells

Abstract: Membrane-electrode-assemblies (MEAs) were fabricated with electrospun nanofiber electrodes containing Johnson-Matthey (JM) HiSpec 4000 catalyst and a Nafion 212 membrane. MEA performance was evaluated in a hydrogen/air fuel cell, where power output was correlated with cathode Pt loading (0.029–0.107 mgPt/cm2) and changes in fuel cell temperature (60°C and 80°C), pressure (up to 3.0 atm), and feed gas flow rates. In all experiments, the nanofiber anode had a fixed Pt loading of 0.10 mg/cm2. The mass activity (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…Refs. 5,7,8,11,12. Even for conventional electrodes, the oxygen reaction order has usually been reported only at open circuit voltage, e.g. Refs.…”
mentioning
confidence: 99%
“…Refs. 5,7,8,11,12. Even for conventional electrodes, the oxygen reaction order has usually been reported only at open circuit voltage, e.g. Refs.…”
mentioning
confidence: 99%
“…2 In a series of recent papers, Pintauro and coworkers have shown that an electrospun nanofiber cathode, composed of Pt/C particles and a binder of Nafion + poly(acrylic acid) (abbreviated as PAA) performs remarkably well in a hydrogen/air proton exchange membrane fuel cell. [3][4][5] For example, a nanofiber electrode MEA with 0.055 mg Pt /cm 2 at the cathode and 0.059 mg Pt /cm 2 at the anode (Johnson Matthey Pt/C catalyst) produced more than 900 mW/cm 2 at maximum power in a H 2 /air fuel cell at 80…”
mentioning
confidence: 99%
“…17 The excellent performance of nanofiber fuel cell electrodes is attributed to facile oxygen and proton transport to catalytic sites and efficient product water removal, which is a direct consequence of the unique nanofiber electrode morphology, with significant inter-fiber and intrafiber porosity and a well-mixed dispersion of catalyst powder and ionomer binder.…”
mentioning
confidence: 99%